Teori Belajar Humanistik dan Konstruktivistik dalam Perspektif Psikologi Barat dan Islam - Yusi Srihartini; Ela Nurlaela; Inayah Rahmaniyyah; Ani Triwahyuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to comparatively analyze humanistic and constructivist learning theories from Western and Islamic psychological perspectives. This study aims to synthesize the concepts of self-actualization and knowledge construction with the values of fitrah and tauhid (theology) in order to formulate an integrative, holistic, and relevant pedagogical framework for the development of contemporary Islamic education.